Covid-19 Pandemic And Its Likely Effect On Economic Development: An Opinion Survey of Professionals - Kumar, Atul; Gawande, Amol; Brar, Vinaydeep (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The air is full of pessimism. The impact of Covid-19 has been anticipated as more awful than the Great Depression of 1930. Consistently analysts and agency reports are plunging into new bottoms of a tumbledown in economic activities. Indian economy, however, has a somewhat slightly different story to tell at this hour of crisis. The silver lining for the Indian economy originates from a lofty fall in crude oil costs from around $70 per barrel to a record multi-year low of $22 per barrel. They have ascended to levels of around $40 per barrel over the most recent months. This benefit increases can somewhat balance the immediate misfortunes due to Covid-19. Simultaneously, dreams like a $5 trillion economy no longer look even a distant chance. This article checks out the possible effect of Covid-19 on Indian economic development through a survey of 400 professionals the nation over.